Part VII – July 1969 – Communications - Discussion of "Grain Growth and Recrystallization in Thoria-Dispersed Nickel and Nichrorne”* - G. P. Tiwari (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1970)
Recrystallization and grain growth in thoria dispersed nickel and nichrome were recently studied by Webster as a function of temperature and deformation. The unexpected part of these results was that specimens which had received heavier deformation developed greater resistance to recrystallization. Retardation of recrystallization was accompanied by the formation of voids around thoria dispersion. To explain these results, Webster suggested that the formation of void around the particles increased the effective size of thoria particles. This resulted in greater impediment to the grain-boundary migration and as a consequence the recrystallization of the matrix is retarded. In the present note an alternative and more probable explanation for the effect of voids on recrystallization is presented. The exact mechanism of void formation in thoria dispersed nickel or nichrome is not known. However, it is reasonably certain that it must be preceded by the stress concentration in the matrix around thoria dispersion during the deformation.'' The resulting stress concentration must be sufficient enough to supply the surface energy for the new surfaces created. Further, the decrease in the strain energy of the matrix surrounding the potential void nucleus must be larger than the surface energy of the newly created surface. The release of strain energy due to formation of crack results in a strain free cylinder of the material around the voids.13 If the void formation is not localized, at few points only (as is the case here), this process may lead to considerable amount of release of strain energy of the matrix. The pattern of recrystallization behavior of single phase homogeneous matrix as well as the matrix having a second phase dispersion is same except for the fact recovery and recrystallization are more clearly delineated.14 In general, the recrystallization temperature is lowered (i.e., recrystallization is easier) with increase in the amount of cold work. This is due to the increase in stored energy in the matrix with increasing amount of deformation. If somehow there is a relaxation of strain energy in the matrix, the recrystallization should become difficult because of the decrease in the amount of stored energy available for recrystallization. Since the formation of voids leads to a decrease in the strain energy of matrix, the recrystallization of the matrix would be inhibited due to the formation of voids during deformation prior to recrystallization. It has been observed by earlier workers15'16 that the presence of preexisting voids in a matrix retards the recrystallization. The essential issue here is how do the voids act to produce this effect. If the voids influence recrystallization only by blocking the grain boundary migration, then the effect should be maximum when they are present almost exclusively along grain boundary. These conditions are obtained during high temperature deformation. However, the voids produced due to creep along grain boundary are not able to prevent recrystallization17 suggesting that they are not effective in blocking grain boundary movement. Recently it was shown by Davies and Williams that the voids can act as sinks for vacancies." As a result the processes dependent on vacancy diffusion like recovery, recrystallization, dislocation climb, and so forth, will be hindered. This fact may be responsible for inhibition of recrystallization during subsequent deformation and annealing cycles. It is to be noted here that there is a large difference between the density of voids in creep experiments and the other experiments where retarding effect of voids on recrystallization is seen. The voids in former may number up to l04 to l05 per sq cm whereas in latter cases the voids density is typically around 1010 to 1013 per sq cm. It appears that the decrease in supply of vacancies in creep is insufficient to adversely affect the recrystallization due to low void population. The author is grateful to P. Das Gupta and S. P. Ray for helpful discussions. Author's Reply D. Webster Tiwari appears to have misunderstood the nature of grain boundary-particle interactions. Tiwari (quoting Cahn) states that second phase particles become more effective as they become smaller, therefore as the voids in TDNiC make the thoria particles effectively bigger their ability to resist grain boundary movement is impaired. This particle size argument was originally proposed in the form of an equation by Zener 20 years agol9 and is not necessarily valid as is discussed below. However, assuming it is valid, it predicts a greater boundary restraining effect by smaller particles simply because their combined cross sectional area is greater at a constant volume. If the number of particles remains the same and their effective size increases, as in the present case, Zener's equation predicts a greatly reduced grain size. This is because the effect